Compostos polifenólicos do kino de Eucalyptus citriodora - Freitas,Marinalva Oliveira (2007)
Phytochemical analysis of the kino of Eucalyptus citriodora led to the isolation of 1-O,2-O-digaloil-6-O-trans -p-cumaroil-beta-D-glucopyranoside, 1-O-trans-p-cumaroil-6-O -cinamoil-beta-D-glucopyranoside, alpha and beta 6-O-trans-p-cumaroil-D-glucopyranoside, 7-methylaromadendrin-4'-O-6''- trans-p-cumaroil-beta-D-glucopyranoside, aromadendrin, aromadendrin-7-methyl-ether, naringenin, sakuranetin, kaempferol-7-methyl-ether and galic acid. Structural elucidation of the isolated compounds was established on the basis of spectral data, particularly by the use of 1D NMR and several 2D shift correlated NMR pulse sequences (¹H,¹H-COSY, HMQC, HMBC).